(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
Zinc oxide (ZnO) was prepared by pulsed laser deposition(PLD) using Q-Switching Nd: YAG laser with =Nd:YAG laser ( a=1064 nm , f=6heposotion NE (ZnPc) THIN FILMS PREPARED BY PULSED LASER DEPOSITION 1064 nm, Repetition rate (f )= 6 Hz , and Energy (E) = 500 mJ at room temperature under vacuum condition with torr. The optical properties included the absorption coefficient, extinction coefficient, index of refractive for the films of ZnO was evaluated and the results are discussed. The energy band gap of thin-film ZnO 3 (eV) at room temperature. The optical transition was found to be direct and allowed transition. Moreover, UV–visible spectra were used to evaluate the ZnO energy gap. FTIR spectra for ZnO used to the presence of Zn-O bonding.